Re-Engineering Strategi Operasi Guna Optimalisasi Produksi Tambang Darat Studi Kasus PT Timah (Persero) Tbk (The Indonesian Journal of Business Administration, 2013)
Production of tin from inland mining is still the mainstay source of tin ore production for PT Timah, the majority of tin ore mining on land in cooperation with partners, but the production of tin ore mining land PT Timah, steadily declining since the change operations strategy inland mining beginning February 2012. Implementation of the Law No. 4 of 2009 on mineral and coal mining, and energy and mineral resources minister enforcement number 28 on the implementation of mining services mineral and coal, causing PT Timah must change its strategy of partnering inland mining operations strategy compensation tin ore being mining equipment rental system. This study uses data analysis of tin ore production in 2012, , external and internal environmental analysis, PESTLE, Porter’s Five Forces Model, SWOT analysis, and interviews with stakeholders to establish the root causes reduced tin ore production of inland mining, which is due to the weak of the PT Timah role in mining operations and because have not been competitive compensation mining equipment rental and purchase price ore mines by the collector in the local market.To optimize the production of tin ore from inland mines it is necessary to re-engineering operations strategies to improve the role of PT Timah by increasing turjawasli inland mining operations and make adjustments to compensate mining equipment rental, as well as re-engineering partnership focused on the improvement of mutualisme relations by enhancing partnerships mutual trust, interdependence, shared resources, and the improvement of supply chain inland mining operations partners. With the re-engineering operating strategy and mining equipment lease compensation adjustment, and improvement partnerships is expected tin ore production to inland partners mining can be controlled and can increase the production of tin ore from inland mines.